Machine vision : theory, algorithms, practicalities - Davies, E. R. (Signal processing and its applications., 1997)
This book provides a detailed background to machine vision, a subject that has evolved to embrace a diverse range of topics. With an emphasis on the theory underpinning practicalities, the book covers the area of image processing, image analysis and machine/computer vision, including automated visual inspection.